Amphipods (exclusive of Pontoporeiidae) of Southeastern Wisconsin - (:unkn) unknown (My University, 1995)
Eight species of amphipods in the families Crangonyctidae (five species), Gammaridae (two species) and Hyalellidae (one species) are recorded here from a 21 county area in southeastern Wisconsin. Excluded from this survey were members of the family Pontoporeiidae, deepwater species previously collected in this region only from Lake Michigan and Green Lake (Juday and Birge 1927). In the species treatments we combine data from our fieldwork with information given in Bousfield (1958), Holsinger (1972), and other literature as cited.
Keywords: Crangonyctidae; Gammaridae; Hyalellidae; amphipods; Southeastern Wisconsin